A formalism to investigate the optimal transmit efficiency in radiofrequency shimming. (28th July 2020) - Georgakis, Ioannis P.; Polimeridis, Athanasios G.; Lattanzi, Riccardo
Abstract : Transmit efficiency specifies the amplitude of the magnetic resonance excitation field produced over a region of interest with respect to the radiofrequency (RF) power deposited in the sample. This metric is highly important at ultra‐high field magnetic resonance imaging (≥7 T), where excitation inhomogeneities and electric field interference effects could prevent achieving the desired flip angle distribution while satisfying the power safety limits. The aim of this work was to introduce an approach to calculate a theoretical upper bound on the transmit efficiency (OPTXE) for RF shimming, independent from any particular coil design. We computed the OPTXE for head‐mimicking uniform spherical samples and a realistic heterogeneous head model by maximizing the square of the net transmit field per unit power deposition. The corresponding RF shimming weights were used to combine the analytical surface current modes into ideal current patterns. OPTXE grew monotonically as the target excitation voxel approached the surface of the object, and overall decreased at higher field strengths, presenting similar trends in both the uniform sphere and heterogeneous head model. Arrays with an increasing number of loops could closely approach OPTXE in the central region of the object, but performance decreased closer to the surface and at higher magnetic field strengths. The performance of 32 loops for a two‐dimensional excitation region at 7 T increased from 34% to 93% when they were arranged based on the shape of the ideal current patterns. OPTXE provides an absolute reference to evaluate coil designs and RF shimming algorithms, whereas ideal current patterns could serve as guidelines for novel coil designs at ultra‐high field. The uniform sphere model enables rapid analytic simulations and provides a good approximation of the OPTXE distribution in a realistic heterogeneous head model with comparable dimensions. Abstract : We introduced a formalism to calculate a theoretical upper bound on the transmit efficiency achievable by any coil for a given sample and excitation region. The optimal transmit efficiency was similar for a uniform sphere with average brain electrical properties and a realistic heterogeneous head model with comparable dimensions. The absolute performance of finite arrays, defined as the achieved percentage of the optimal transmit efficiency, increased with the number of transmit channels and decreased at higher magnetic field strength.